The historian's toolbox a student's guide to the theory and craft of history - Williams, Robert C (New York Routledge, 2020)
"The Historian's Toolbox introduces students to the theory, craft, and methods of history and equips them with a series of tools to research and understand the past. Written in an engaging and entertaining style, and filled with fascinating examples, this best-selling "how to" book opens up an exciting world behind historical research and writing. This fourth edition expands the repertory of tools and techniques available to students entering the workshop of history. These include materials on the Kennedy assassination, the litigation of Van Gogh's Night Café, local town histories, contemporary history, Twitter, and the contemplation of the end of history as well as the Sixth Extinction in a new epilogue. The book demonstrates the relevance and expanding possibilities of the study of history in our cacophonous information age of tweetstorms and fake news; it emphasises the increasing value of critical thinking, facts and evidence in the face of political lies and conspiracy theories. Material added to the fourth edition will resonate with a new generation of computer-literate readers in the face of climate change. The Historian's Toolbox continues to be a seminal text for supporting students throughout their study of history and an accessible teaching tool for instructors."--
Part I. The Craft of History -- The Past -- Story -- History -- Metahistory -- Antihistory -- The Present -- The Future -- Part II. The Tools of History -- Doing History: An Overview -- Choosing a Good Paper Topic -- Reading History -- Taking Notes -- How to Write a Good History Paper -- Sources and Evidence -- Primary and Secondary Sources -- Primary Source: The Wannsee Protocol (1942) -- Secondary Source: Denying History: Who Says the Holocaust Never Happened and -- Why Do They Say It? (2000) -- Summary -- Documents -- A Revolutionary War Ancestor's Pension Application (1832) -- Maps -- Sebastian Munster's Map of the Americas, c. -- Artifacts -- Digging Ancient Moscow -- Images -- Sharpshooter's Home or Photographer's Studio? -- Cliometrics: Using Statistics to Prove a Point -- The Black Population of Colonial America -- Genetic Evidence -- Welsh and Basques, Relatively Speaking -- Thomas Jefferson and Sally Hemings-What's My Line? -- Credit and Acknowledgment -- Notes -- Bibliography -- Styling Your Bibliography -- Types of Bibliographies -- A Selective, Annotated Bibliography -- Acknowledging Sources and Avoiding Plagiarism -- Professional Plagiarism: How Not to Do History -- Narrative and Explanation -- The Language of the Historian -- Paul Revere and the New England Village -- Chronology -- The Life of Margaret Fuller -- Narrative -- Pickett's Charge at Gettysburg -- Argument -- "'Little Women' Who Helped Make This Great War" -- Causation -- The Reasons Why -- Explaining the Mann Gulch Fire of August 5, -- Interpretation -- Reviewing History -- Bellesiles's Arming America -- Historical Revision -- The Denmark Vesey Slave Conspiracy (1822) -- Historiography -- World War II -- Women's History: The Leo Frank Case -- Speculation -- 1 Historical Speculation -- Will the Real Martin Guerre Please Get an Identity? -- History as Fiction -- The Soldier Who Never Was -- Conspiracies -- Who Really Really Killed Lincoln? -- Forgeries and Facsimiles -- Is a Document Genuine? -- Is a Collection of Documents Authentic? -- How Can Forgeries Influence History? -- Is a Newly Discovered Collection by a Well-Known Author Authentic? -- If It Is a Forgery, Who Is the Forger? -- Fiction as History -- Film as History: Fact or Fiction? -- Films Can Help the Historian Understand the Past -- Films Can Hinder Our Understanding of the Historical Past -- Part III. The Relevance of History -- Everyday History -- Studying Ordinary People -- The Burgermeister's Daughter -- Everyone's a Historian -- Local History. A Tale of Two Towns -- Oral History -- The Perils of Memory -- Interviewees and Interviewers -- The WPA Slave Narratives -- Techniques of Oral History -- Material Culture -- Spirits in the Material World Richard Bushman and The Refinement of America -- Studying Material Culture -- Provenance and Ownership. Tracing Stolen Art -- Public History -- History Beyond the Ivory Tower -- History and the Public -- The Enola Gay Controversy -- Event Analysis -- History in Real Time -- The Iraq War: Munich, Mukden, or Mexico? -- New Tools: GIS and CSI -- Spatial History: Geographic Information Systems -- Killer App: Crime Scene Investigation Forensics -- History on the Internet -- Using the Internet: Promises and Pitfalls -- Wikipedia and "Wikiality" -- Blogging the Past (and Present) -- TMI: Too Much Information -- History as Information -- Hacking History: The Deluge of WikiLeaks -- Private Parts: The Intrusion of History -- Twitter -- Epilogue: The End of History?
Includes bibliographical references and index.
Keywords: History -- Methodology; History -- Research